RANCANG BANGUN SISTEM INFORMASI MANAJEMEN DATA SANTRI PADA TAMAN PENDIDIKAN AL-QUR'AN MASJID AD-DU'A BERBASIS LARAVEL - Anis Purnomo; Astria Hijriani; Ossy Dwi Endah Wulansari (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Laravel is a framework based on the PHP programming language that can be used in making web-based applications that are very popular for use ranging from small-scale to large-scale projects. Applications developed using laravel can be used for the benefit of individuals or institutions to facilitate the data management process. The Al Quran Education Park of the Ad-Du'a Mosque as a non-formal educational institution has many students that need to be processed to make it easier for institutional leaders to determine policies. Data processing for students through a web application is considered very easy because it can be done online and more effectively. The data that is processed in this application is student data starting from the registration process to determining the study group. In determining the study group, the system admin will classify the data that has been collected from the registration process based on the age range and ability to read the Koran. The process of making this application uses the extreme programming method because this method is quite effective when used in developing small-scale applications. The stages in this method are planning, design, coding, test, then if it is appropriate then release the application. After going through the stages of making an application using this method, a web-based application is produced which can be used to manage student data at the Al-Quran Education Park of the Ad-Du'a Mosque.